Psychology and culture: exploring clinical psychology in Australia and the Malay Archipelago. (7th October 2014) - Geerlings, Lennie R.C.; Thompson, Claire L.; Lundberg, Anita
Abstract : This paper provides landmarks for the study of the historical development and current expansion of academic psychology and clinical psychology education in Australia and three countries of the Malay Archipelago (Indonesia, Malaysia, Singapore). It reviews literature on the history of clinical psychology, and information from universities and psychological associations, and includes an overview of the current providers and forms of psychology education programmes and their curricula. A critical analysis informed by cultural anthropology indicates that psychology has only to a small extent been adjusted to different cultural contexts, while 'western' models of the discipline remain dominant. The neglect of attention to culture in psychology and clinical psychology raises important questions about the future of the discipline in the tropical regions of Australia and the Malay Archipelago.